2016
DOI: 10.1248/bpb.b15-00827
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antitumor Invasive Actions of <i>p</i>-Cymene by Decreasing MMP-9/TIMP-1 Expression Ratio in Human Fibrosarcoma HT-1080 Cells

Abstract: p-Cymene (4-isopropyltoluene) has been reported to have beneficial actions such as anti-inflammatory and antinociceptive activities. To evaluate whether p-cymene exhibits antitumor invasive actions, we examined the effects of p-cymene on the production of matrix metalloproteinase 9 (MMP-9)/gelatinase B and tissue inhibitor of metalloproteinases-1 (TIMP-1) in human fibrosarcoma HT-1080 cells. p-Cymene was found to dose-dependently inhibit the 12-O-tetradecanoylphorbol 13-acetate (TPA)-augmented production and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The anti-inflammatory activity of p-cymene at least partly justifies its antinociceptive activity, as recorded in several in vivo studies performed on murine model systems [ 8 , 10 , 11 ]. Moreover, recent investigations report the antitumor activity of p-cymene and metal p-cymene complexes such as rutenium (II)- and osmium (II)-p-cymene complexes, which inhibit tumor proliferation through an antiangiogenic mechanism, cancer cell cytotoxicity, and anti-adhesion activity [ 12 , 13 , 14 ]. p-Cymene is the main antimicrobial compound in thyme, and a large body of evidence suggests that this monoterpene possesses antibacterial, antiviral and antifungal activities.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory activity of p-cymene at least partly justifies its antinociceptive activity, as recorded in several in vivo studies performed on murine model systems [ 8 , 10 , 11 ]. Moreover, recent investigations report the antitumor activity of p-cymene and metal p-cymene complexes such as rutenium (II)- and osmium (II)-p-cymene complexes, which inhibit tumor proliferation through an antiangiogenic mechanism, cancer cell cytotoxicity, and anti-adhesion activity [ 12 , 13 , 14 ]. p-Cymene is the main antimicrobial compound in thyme, and a large body of evidence suggests that this monoterpene possesses antibacterial, antiviral and antifungal activities.…”
Section: Introductionmentioning
confidence: 99%
“…The differences between the IC 50 values of F-PSEO and L-PSEO are attributed to both compositional and quantitative variations among these oils. The cyclic monoterpene p -cymene, that constitutes a 27.76% (by SPME, 1.33% by hydrodistillation) of the flower oil compared to 5.56% (SPME, 0.1%-hydrodistillation) in L-PSEO, has been reported to exhibit strong antitumor invasive and metastatic actions towards the human fibrosarcoma HT-1080 cells through inhibition of matrix metalloproteinase 9 (MMP-9) along with the suppression of ERK1/2 and p38 MAPK [50]. The cyclic monoterpene α-phellandrene, comprises 13.59% (SPME, 1.74%-hydrodistillation, compared to 1.08% and 0.36% in L-PSEO, respectively), induces apoptosis through the mitochondria-dependent pathway, cell cycle arrest at G0/G1 phase and production of reactive oxygen species (ROS) in murine WEHI-3 leukemic cells [51].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly obvious with the finding that the general caspase-inhibitor is only able to reverse ∌30% of the oil induced apoptosis in MDA-MB-2 31 compared to ∌60% in MCF-7 cells. The fact that the essential oils of P. spinosa contain compounds that promote cell death by autophagy [53], activation of MAPKs [50], production of ROS [51] and cell cycle arrest [51], proposes that they may also contribute to the cytotoxicity of F-PSEO and L-PSEO.…”
Section: Discussionmentioning
confidence: 99%
“…The movement-evoked pain test did not show significant inhibition in the reduction of paw utilization by the mice (supplementary material). However, another study (Li et al, 2016) demonstrated that PC has the antitumor effect due to the modulation of ERK1/2 and p38 MAPK signal pathways in tumor cells.…”
Section: Accepted Manuscriptmentioning
confidence: 99%